Exact analytical solution for MHD flow and heat transfer of Jeffrey fluid over a stretching sheet with viscous dissipation - Wahid, N. S.; Hafidzuddin, M. E. H.; Arifin, N. M.; Turkyilmazoglu, M.; Rahmin, N. A. A. (2019)
The magnetohydrodynamic (MHD) flow and heat transfer of Jeffrey fluid over a stretching sheet with the presence of viscous dissipation is studied analytically. The governing partial differential equations are transformed to non-linear ordinary differential equations with the facilitation of sophisticated similarity variables, which are then being solved analytically by using exact analytical method. The effects of the physical parameters on the velocity and temperature distributions are presented through graphs, discussed and compared with the previous work of the same problem that has been solved numerically to verify the present analytical method being used. The skin friction coefficient and the local Nusselt number are also computed and analyzed.